MORAL JUSTICE AND SOCIAL TO CHILD IN FAMILY POLYGAMY IN PUBLIC MALAY CITY OF MEDAN - Sofyan Suri; Pagar Pagar; Mhd. Syahnan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
This study aimed to view the natural moral justice and justice social to the child in the family results of polygamy. Data collection techniques used are observation and interviews. The informants in this study were only 50 people. The research findings in this article are the results of wedding polygamy; they have the right to moral justice because of a value of 68.78%. This fact means that the father already almost approaches perfection in fulfilling his obligations to the child's rights. Whereas in a manner justice social, according to children from wedding polygamy for Public Malays in Medan City yet Can apply fair to they as member family, because value obtained is 27.45%. According to the children, the father is still dominant on children, confident in giving the right child evenly. However, the fathers disputed this assessment because, according to the fathers, social injustice is not the same, but it provides services according to the needs and circumstances of the father.